Application of noncanonical amino acids for protein labeling in a genomically recoded Escherichia coli - Kipper, Kalle; Lemke, Edward A. (ACS synthetic biology, 2016)
Small synthetic fluorophores are in many ways superior to fluorescent proteins as labels for imaging. A major challenge is to use them for a protein-specific labeling in living cells. Here, we report on our use of noncanonical amino acids that are genetically encoded via the pyrrolysyl-tRNA/pyrrolysyl-RNA synthetase pair at artificially introduced TAG codons in a recoded E. coli strain. The strain is lacking endogenous TAG codons and the TAG-specific release factor RF1. The amino acids contain bioorthogonal groups that can be clicked to externally supplied dyes, thus enabling protein-specific labeling in live cells. We find that the noncanonical amino acid incorporation into the target protein is robust for diverse amino acids and that the usefulness of the recoded E. coli strain mainly derives from the absence of release factor RF1. However, the membrane permeable dyes display high nonspecific binding in intracellular environment and the electroporation of hydrophilic nonmembrane permeable dyes severely impairs growth of the recoded strain. In contrast, proteins exposed on the outer membrane of E. coli can be labeled with hydrophilic dyes with a high specificity as demonstrated by labeling of the osmoporin OmpC. Here, labeling can be made sufficiently specific to enable single molecule studies as exemplified by OmpC single particle tracking.